1086 The association between occupational asthma and skin sensitisation to low-molecular weight agents: a systematic review. (24th April 2018) - Tsui, Hung-Chang; Sadeleer, Laurens De; Vanoirbeek, Jeroen; Hoet, Peter; Nemery, Benoit
Abstract : Introduction: Occupational asthma is one of the most frequent forms of work-related lung disease in industrialised countries. Mounting evidence suggests that low-molecular-weight (LMW) agents, such as isocyanates and anhydrides, are linked to the development of occupational asthma through skin exposure and sensitisation. This review aimed to provide an overview of all reported LMW agents exhibiting evidence of inducing respiratory sensitisation via skin exposure. Methods: We conducted a database search with MEDLINE/PubMed and Embase. We included animal studies that investigated the potential of LMW agents to elicit respiratory responses after airway challenge after prior skin sensitisation; epidemiological studies that evaluated the association between skin exposure to LMW agents and occupational asthma; and case reports of occupational asthma and concurrent allergic dermatitis caused by LMW agents. One person conducted the search and first screening. Two reviewers independently performed the final selection using full-text reports. Results: Of 6949 identified articles, 306 studies were included: 83 animal studies, 45 epidemiological studies, 99 case reports, 37 reviews and 38 other types of articles. The 83 animal studies concerned 36 different LMW agents, with trimellitic anhydride (TMA), toluene diisocyanate (TDI), and diphenylmethane diisocyanate (MDI) being studied most frequently, mostly in BALB/c mice, Brown Norway rats, and Hartley guinea pigs. The appraisal of the human studies is ongoing. Discussion: This systematic review summarises the recent research progress on the association between asthma and skin sensitisation to LMW agents. An improved evidence-based understanding in this field should facilitate the control of exposure to chemical sensitizers in the workplace. Moreover, this systematic review will contribute to improve our understanding of the pathogenesis of non-atopic asthma in general.